1988
DOI: 10.1128/jb.170.4.1445-1451.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the egl gene of Pseudomonas solanacearum and analysis of its role in phytopathogenicity

Abstract: The egl gene of Pseudomonas solanacearum was cloned on a cosmid and expressed in Escherichia coli. Restriction endonuclease mapping, transposon mutagenesis, and subclone analysis showed that the egl gene was located on a 2.7-kilobase XhoI-SalI P. solanacearum DNA fragment. Immunoabsorption experiments and sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis showed that the egl gene encodes the 43-kilodalton endoglucanase that is the major excreted endoglucanase of P. solanacearum. In E. coli, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0
6

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 24 publications
1
142
0
6
Order By: Relevance
“…Plant pathologists have generally felt that cellulases are not particularly important in pathogenesis, since extensive cellulose degradation typically occurs only late in infection, if at a11 (Cooper, 1984). However, when the major endoglucanase genes of the phytopathogenic bacteria Pseudomonas solanacearum and Xanthomonas campestris pv campestris were disrupted, virulence decreased (Gough et al, 1988;Roberts et al, 1988). …”
Section: Cellulasementioning
confidence: 99%
“…Plant pathologists have generally felt that cellulases are not particularly important in pathogenesis, since extensive cellulose degradation typically occurs only late in infection, if at a11 (Cooper, 1984). However, when the major endoglucanase genes of the phytopathogenic bacteria Pseudomonas solanacearum and Xanthomonas campestris pv campestris were disrupted, virulence decreased (Gough et al, 1988;Roberts et al, 1988). …”
Section: Cellulasementioning
confidence: 99%
“…A 10 mL suspension of Pta (OD 600 ¼ 1) was sprayed on the leaves of N. benthamiana plants at 1 week after leaf infiltration with the chemical BTH (Figs 1 and 3). The severity of R. solanacearum symptoms was scored from 0 to 5 as follows: 0, no leaves wilted; 1, 1-20 % of leaves wilted; 2, 21-40 % of leaves wilted; 3, 41-60 % of leaves wilted; 4, 61-80 % of leaves wilted; and 5, 81-100 % of leaves wilted (Roberts et al, 1988). The severity of Pta symptoms was scored from 0 to 5 as follows: 0, no symptoms; 1, yellowish colour; 2, chlorosis only; 3, partial necrosis and chlorosis; 4, necrosis of the inoculated area and expanded chlorosis; and 5, complete necrosis of the inoculated area.…”
Section: Pathogen Challengementioning
confidence: 99%
“…Ralstonia solanacearum, Pta and Psy were grown on solid Casamino acid-Peptone-Glucose (CPG) and King's B medium respectively containing 100 lg mL -1 rifampicin for selection at 30 C for 2 d, scraped off the plates and re-suspended in 10 mM MgCl 2 (Roberts et al, 1988;Song et al, 2015). A 50 mL aliquot of bacterial suspension of R. solanacearum at OD 600 ¼ 1 was freshly prepared and drenched into the root system of every N. benthamiana seedling (Chandrasekaran et al, 2016).…”
Section: Pathogen Challengementioning
confidence: 99%
“…solanacearum secretes several CWDEs, including three polygalacturonases (PehA , PehB and PehC) [27,28], an endoglucanase (Egl) [29], a pectin methylesterase (Pme) [30], and a cellobiohydrolase (CbhA) [31]. Gene disruption analysis revealed that Egl, PehA, PehB and CbhA, each contribute to the pathogen's ability to cause wilt [31][32][33].…”
Section: Cell-wall-degrading Enzymes (Cwdes) and Type II Secretion Symentioning
confidence: 99%